A Review on Chemical Pretreatment of Lignocellulosic Biomass for the Production of Bioproducts: Mechanisms, Challenges and Applications - Areeya, Sukunya; Panakkal, Elizabeth Jayex; Sriariyanun, Malinee; Kangsadan, Tawiwan; Tawai, Atthasit; Amornraksa, Suksun; Hartley, Unalome Wetwattana; Yasurin, Patchanee (Applied Science and Engineering Progress, 2023)
Excessive dependence on fossil resources to supply the increased energy demands has led to unsustainable growth. Hence, there is a necessity to shift our reliance from non-renewable to renewable resources. In this scenario, lignocellulosic biorefinery gains its importance because lignocellulosic biomass can be converted into various value-added products. However, biomass pretreatment is necessary due to the recalcitrant nature of the biomass. Various pretreatment techniques are employed to convert biomass into a more amenable structure to be utilized in the further steps of biorefinery. Hence, this review concentrates on different chemical pretreatment techniques used currently on biomass along with their modes of action on the biomass. This review will provide a detailed concept of various chemical pretreatments and the recent developments in pretreatment techniques. Despite this, the limitations of the current pretreatment strategies and the difficulties in their industrial applications are also discussed, which could provide innovative ideas to overcome these issues.